Carbon dots as a luminescence sensor for ultrasensitive detection of phosphate and their bioimaging properties. (9th September 2014) - Xu, Jingyi; Zhou, Ying; Cheng, Guifang; Dong, Meiting; Liu, Shuxian; Huang, Chaobiao
Abstract Highly blue fluorescence carbon dots were synthesized by one‐step hydrothermal treatment of potatoes. The as‐obtained C‐dots have been applied to bioimaging of HeLa cells, which shows their excellent biocompatibility and low cytotoxicity. The results reveal that C‐dots are promising for real cell imaging applications. In addition, the carbon dots can be utilized as a probe for sensing phosphate. Copyright © 2014 John Wiley & Sons, Ltd.